Effects of immune cells on ischemic stroke and the mediating roles of metabolites - Hu, Haoxiang; Zhou, Mi; Zhao, Yunhan; Mao, Jiesheng; Yang, Xiaokai (Frontiers in Neurology, 2024)
Objective Previous studies have not shown an association between IgD-CD24-B-cell absolute count (IgD-CD24-AC) and ischemic stroke (IS). Our study aimed to assess the causal effect of IgD-CD24-AC on IS and to explore the role of ascorbic acid 2-sulfate (AA2S) as a potential mediator. Methods Our study was based on the largest available genome-wide association study (GWAS). Inverse variance weighting (IVW), MR–Egger, weighted median (WMN), simple mode, and weighted mode methods were used to assess causal effects, with IVW as the primary outcome. Subsequently, we further performed a two-step MR analysis to evaluate whether AA2S mediated this causal effect. In addition, several sensitivity analyses were conducted to evaluate heterogeneity, including Cochran’s Q test, the MR–Egger intercept test, the MR-PRESSO global test, and the leave-one-out analysis. Results Using the IVW approach, the risk ratio of IgD-CD24-AC to IS was estimated to be 1.216 (95% CI = 1.079–1.371, p = 0.001). This result was supported by the WMN method (OR = 1.204, 95% CI = 1.020–1.421, p = 0.028) and the MR–Egger method (OR = 1.177, 95% CI = 0.962–1.442, p = 0.133). We also observed the same trend with the simple model and weighted model. Furthermore, the proportion of genetically predicted IgD-CD24-AC mediated through AA2S levels was 3.73%. Conclusion Our study revealed a causal relationship between IgD-CD24-AC and IS, a small part of which was mediated by AA2S. These findings offer critical insights for developing immune-targeted therapies in the future and lay a strong foundation for advancements in precision medicine.